KEPUASAN KERJA MAHASISWA MAGANG : STUDI LITERATUR - Vaniasari, Shafira; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to analyze the effect of job characteristics and work environment characteristics on job satisfaction. This study consists of two independent variables and one dependent variable. The independent variables in this study are job characteristics and work environment characteristics. The dependent variable in this study is job satisfaction. Sampling was carried out using a purposive sampling method. Data collection was carried out by distributing online questionnaires to intern students at E-commerce companies. A total of 135 interns have participated in this study. Data analysis was performed using structural equation modeling analysis with SmartPLS 3.2.9. The results of this study indicate that job characteristics and work environment characteristics have a significant positive effect on job satistfaction.